Effects of Laser at 810 Nm on Wound Healing in Albino Mice - Funjan, Mawada M. (Iraqi Journal of Science, 2020)
Many researches focused on laser therapy of wound healing in different animal models due to the lack of a standard protocol in the application of such phototherapy. Objective: To study the effects of 810nm laser at a constant irradiance of 41.63 mw/cm2 and exposure (illumination) time of 5,15 minutes on wounds created on Albino mice (BALB/c). Skin wound with elliptic shape and full thickness was created on the dorsal side of ‘45 mature male albino mice. Irradiated animals were divided into two main groups based on irradiation time, the first was irradiated for 5 min and the second for 15 min, each was subdivided into three subgroups (n=5) according to number of treatment days (3, 5 and 10 days). Both treated and respective control (n=15) subgroups were sacrificed on days 3, 5 and 10 posttreatment. Laser therapy was applied using a 810 nm diode laser with a continuous wave, an output power of 400 mw, and irradiance of 41.63. The 5 min dose was 12 .5 J/cm2, whereas the 15 min dose was 37.4 J/cm2. The shape of the laser beam was fitted with a convex lens as ‘beam expander’ to irradiate a circular area of 3.4 cm diameter. Laser therapy was started after surgery and repeated for 3, 5 and 10 days, while its effects were examined by histological evaluation. Results: At day 3 of treatment with near infrared 810nm laser at doses of 12.5J/cm² and 37.4J/cm², there was no evidence of wounds healing in irradiated groups which showed no differences with the respective control groups. At day 5 of treatment, the results showed an important increase in the scores of the parameters of wound healing (formation of granulation tissue and collagen deposition) in the irradiated groups. Near infrared 810nm laser had photobiostimulation effects on wound healing at irradiance of 41.63mW/cm² and doses of 12.5J/cm² for 5 minutes and 37.4J/cm² for 15 minutes exposure time. A complete picture of wound healing response appeared in all irradiated groups within 10 days of treatment, as expressed by complete ‘re-epithelialization’, moderate granulation tissue formation, and presence of collagen fibers, while incomplete wound healing response was observed in un-irradiated control groups within the same period. The study showed that 810 nm laser therapies had significant effects on wound healing, especially at a dose of 37.4J/cm².